Avaliação clínico-epidemiológica dos pacientes internados na emergência aguardando UTI - Santos, Fernanda Ribeiro Quintino dos (2018)
The phenomena of overcrowding in emergency rooms (ER) and intensive care units (ICU) is a great concern especially in low-middle income countries. Objective: To know the impact of delayed admissions of patients awaiting for vacancy in the ICU in an overcrowded emergency room of a public hospital. Methods: Prospective, cohort study (Medical School - São José do Rio Preto / SP). Data were obtained from patients admitted in the ER with documented request for admission to the 27-bed medical-surgical ICU. Patients were categorized into tertiles according to waiting time in ER for a ICU bed (group 1: < 637 minutes, group 2 - 637 to 1602 minutes, group 3- > than 1602 minutes). Results: A total of 6176 patients were treated in the emergency room, of whom 1913 (31%) had a bed request in the ICU. A total of 209 patients (11%) from the emergency room were admitted to the mixed ICU of this institution. A median hospital stay in ER was 17 hours [9 to 33 hours]. Patients who were admitted to the ICU faster were younger (group 1, 48 years (median), 28-61 years [25% -75%], group 2, 52 years [31-60 years], group 3, 58 years [44-72 years]; (p = 0.001)). The length of hospital stays increased significantly in group 3 (18 days, [9-31 days]) compared to group 1 (10 days, [4-21 days]) and group 2 (11 days, [6.5-20 days]; (p = 0.002). The mortality rate increased from 31% in the first group to 38% in the third group (p = 0.639). Resources utilization to public health system was higher in groups 2 and 3; $20,794.00 ( 95% CI $15,500.00 - $26,000.00) per patient in group 1, $21,700.00 (95% CI $16,600.00 - $26,800.00) per patient in group 2, and $24,677.00 (95% CI $19,600.00 - $29,740.00) per patient in group 3. Non-survivors used more resources than survivors. Hospitalization for infection / sepsis was an independent predictor for prolonged ICU stay (OR 2.75 95% CI 1.38-5.48, p= 0.004). Conclusion: Delayed admission was associated with prolonged hospital length-of-stay and increasing resource utilization.